2015
DOI: 10.1128/cvi.00148-15
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Antigen-Specific Immune Response to Vaccines in Children with Antibody Production Defects

Abstract: The impaired synthesis of antigen-specific antibodies, which is indispensable for an adaptive immune response to infections, is a fundamental pathomechanism that leads to clinical manifestations in children with antibody production defects. The aim of this study was to evaluate the synthesis of antigen-specific antibodies following immunization in relation to peripheral blood B cell subsets in young children with hypogammaglobulinemia. Twenty-two children, aged from 8 to 61 months, with a deficiency in one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…50-fold increase in Typhi Vi IgG and 13-fold increase in pneumococcal IgG) was diagnosed with hypogammaglobinaemia and the other patient (with a greater than or equal to fivefold increase in Typhi Vi IgG and a sevenfold increase in pneumococcal IgG) was diagnosed with IgG subclass deficiency. Residual responses to vaccines, sometimes near to those observed in a normal population, have been shown previously in patients with hypogammaglobinaemia [16][17][18]. Total serum immunoglobulin levels alongside the functional information offered by vaccination responses and clinical assessment of infection burden are required to evaluate humoral immune function [19].…”
Section: Discussionmentioning
confidence: 87%
“…50-fold increase in Typhi Vi IgG and 13-fold increase in pneumococcal IgG) was diagnosed with hypogammaglobinaemia and the other patient (with a greater than or equal to fivefold increase in Typhi Vi IgG and a sevenfold increase in pneumococcal IgG) was diagnosed with IgG subclass deficiency. Residual responses to vaccines, sometimes near to those observed in a normal population, have been shown previously in patients with hypogammaglobinaemia [16][17][18]. Total serum immunoglobulin levels alongside the functional information offered by vaccination responses and clinical assessment of infection burden are required to evaluate humoral immune function [19].…”
Section: Discussionmentioning
confidence: 87%
“…Although simple and robust, titer measurements represent an average of the present IgG repertoire. Moreover, Ab titer only partly correlates with protection, even for Ab-mediated vaccines (13). Indeed, this measure is not suitable to resolve the full complexity of the humoral response in terms of biochemical (.10 3 different Abs in serum) (14), biophysical (affinity, specificity), or temporal dimensions (long half-lives, large distribution volume) (15,16).…”
mentioning
confidence: 99%
“…Transitional B cells, considered an intermediate state between immature and mature B cells with reduced proliferative and functional capabilities were also studied. Piatosa et al reported increased number of transitional B cells associated with granuloma formation and enteropathy in children with CVID, and others have shown increased relative frequencies in children aged from 24 to 60 months with unspecific hypogammaglobulinemia . The increased number of transitional B cells in UH group may reflect a more activated status of the immune response in children with hypogammaglobulinemia without serious complications.…”
Section: Discussionmentioning
confidence: 91%
“… Figure S1. (A) Facs gating strategy to analyze B cells (CD19 + ) and B‐cell subsets : naive (N): CD27 − IgD + ; non‐switched memory (NS): CD27 + IgD + ; switched memory (SW): CD27 + IgD − , atypical (A): CD27 + IgD − ; CD21 low , transitional (TR): CD38 ++ IgM ++ , plasmablast (PB): CD38 ++ IgM − and CD24 hi CD38 hi B cells; (B) CD4 + and CD8 + T‐cell subset, effector cells (Eff): CCR7 − CD45RA + , naive (N): CCR7 + CD45RA + , central memory (CM): CCR7 + CD45RA − and effector memory (Em): CCR7 − CD45RA − .…”
mentioning
confidence: 99%